Prognostic Significance of Dynamic Lymphocyte Changes in Esophageal Cancer Patients Receiving Fluorouracil-Cisplatin Combined with Radiotherapy: A Systematic Review and Meta-Analysis - Cong Zhang MM; Zhi Yang MM; Jie Li MM; Lina Zhao MD, PhD (Technology in Cancer Research & Treatment)
Introduction Chemoradiotherapy (CRT) is important to the esophageal cancer (EC) management. However, the predictive value of lymphocyte-related parameters, such as lymphocyte count (L), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR), is not yet fully understood. Moreover, chemotherapy agents like fluorouracil and cisplatin may have an impact on lymphocyte dynamics. This meta-analysis aims to evaluate the prognostic value of these parameters in EC patients undergoing concurrent CRT (eg, radiotherapy combined with fluorouracil and cisplatin), particularly in the context of specific chemotherapy regimens. Methods Electronic databases were comprehensively searched up to September 2023 for research that assesses the prognostic role of lymphocyte-related indicators in EC patients undergoing CRT. Combined Hazard Ratios (HR) were estimated with a random-effects model, supplemented by meta-regression and subgroup analyses for enhanced insights. Results Of the 41 studies selected for qualitative evaluation, 22 were eligible for meta-analysis. These results revealed that increased pre-NLR (HR = 1.87, 95% CI = 1.55-2.26), lower pre-LMR (HR = 1.94, 95% CI = 1.36-2.77), lower dur-L (HR = 1.56, 95% CI = 1.28-1.90), and higher post-NLR (HR = 1.95, 95% CI = 1.08-3.51) predicted poorer overall survival (OS). Lower pre-LMR (HR = 1.73, 95% CI = 1.14-2.65) and lower dur-L (HR = 1.39, 95% CI = 1.14-1.69) were significant predictors of worse progression-free survival (PFS). The predominant chemotherapy regimen analyzed was fluorouracil combined with cisplatin, which significantly influenced lymphocyte counts and ratios during treatment. Conclusions Our meta-analysis indicates that pre-treatment NLR, pre-treatment LMR, during-treatment L, and post-treatment NLR are valuable prognostic biomarkers for EC undergoing CRT, particularly in those treated with fluorouracil and cisplatin. Further investigations are warranted to explore their prognostic implications and therapeutic potential.